FRI0073 Predictive factors for unfavorable outcomes in early rheumatoid arthritis: a prospective multicenter cohort study in argentina. (23rd January 2014) - Casalla, L.; Chaparro del Moral, R.; Rillo, O. L.; Benegas, M.; Dal Pra, F.; Maldonado Ficco, H.; Citera, G.; Catalan Pellet, A.; Berman, A.; Haye Salina, M.; Alvarez, A. C.; Caeiro, F.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is known to have a variable course resulting in a wide range of outcomes, varying from a mild disease causing hardly any impairment to severe disease leading to extensive disability and radiological damage 1, 2 . Objectives: The aim of the present study was to identify predictive factors for unfavorable outcomes in early rheumatoid arthritis patients. Methods: The 1-year outcome of RA patients from a prospective inception cohort (CONAART-Argentine Consortium for Early Arthritis) was assessed. We defined the following 3 criteria for unfavorable outcomes: a clinical course with persistent moderate-high disease activity during the last 6 months (DAS28 average ≥ 3.2, or an increase > 1.2 compared to baseline, or at least one DAS28 >5.1), a disability worsening and a radiological damage increasing (HAQ deterioration within 1 year of ≥ 0.5 points and Simple Erosion Narrowing Score (SENS)- deterioration within 1 year of ≥ 1 points, respectively). Two groups of patients (unfavorable outcome or not unfavorable outcome), were identified for each of the 3 outcome dimensions. Significance of the difference between groups was tested using a Student's t -test, a Mann–Whitney U test, or a chi-square test where appropriate. All baseline parameters (demographic and socioeconomic parameters; comorbidities; disease characteristics; laboratory measures and radiographic measures) for both patient groups were analyzed. To calculate which baseline parameters predict outcome several logistic regression models were constructed. Results: A total of 237 patients were included; 200 (84.4%) were women; 73% rheumatoid factor positive and 71% APCA positive. The mean age was 49 years (SD 12) and the median symptoms duration was 7 months (RIQ 3-12). After one year of follow-up, 141 (59.5%) patients had persistent moderate-high disease activity, 19 (8%) HAQ deterioration and 57 (24.1%) SENS worsening. The prognostic factors for persistent moderate-high disease activity were: medical history of anxiety or depression (OR 3.7; p 0.016), female gender (OR 3.1; p 0.003), and DAS28 (OR 1.3 p 0.005). Among all the factors we found that patients with monoarthritis at baseline had more probability of HAQ deterioration (OR 8.2; p 0.03) and greater values of DAS28 reduced it (OR 0.6 p 0.007). There were not baseline variables associated with radiographic progression. Conclusions: Our study showed that in short-term follow up of early RA patients, different outcomes could be predicted using widely available baseline parameters. References: Arthritis Rheum. 2002;47:383-90. Arthritis Res Ther. 2008;10:R106. Disclosure of Interest: L. Casalla Grant/research support from: Pfizer Argentina, R. Chaparro del Moral : None Declared, O. Rillo : None Declared, M. Benegas: None Declared, F. Dal Pra: None Declared, H. Maldonado Ficco: None Declared, G. Citera: None Declared, A. Catalan Pellet: None Declared, A. Berman: None Declared, M. Haye Salina: None Declared, A. Alvarez: None Declared, F. Caeiro: None Declared, J. Marcos: None Declared, J. C. Marcos: None Declared, L. Catoggio: None Declared, E. Soriano: None Declared, F. Ceccato: None Declared, S. Paira: None Declared, M. O. Leal: None Declared, A. Quinteros: None Declared, G. Salvatierra: None Declared, M. Crespo: None Declared